CERTAINTY FACTOR METHODS IN IDENTIFYING INTERESTS AND TALENTS OF ELEMENTARY SCHOOL CHILDREN AL IKHLAS TAQWA - Fitria, Amanda; Idrus, Said Iskandar Al; Asiah, Asiah; Suryani, Nita; Nabila, Rinjani Cyra (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Psychologists and child education experts always remind the importance of knowing interests and talents from an early age to provide a stimulus to children from an early age, because the provision of the stimulus affects the future of children. This study aims to (1) To make calculations in mathematical models to calculate and analyze the interests of children's talents using applications. (2) To create a web-based information system that can facilitate teachers and parents in determining the interests of children's talents at the Al-Ikhlas Taqwa Plus Elementary School using the Certainty Factor method. The method used in this research is the research and development (R&D) method using the certainty factor. The population in this study were all students of SD Plus Al Ikhlas Taqwa Medan T.P 2021/2022 starting from grades 3-6. Sampling was done by purposive sampling technique. Data collection was carried out by interviews, material expert test questionnaires, and media experts, and the results of the children's talent interest questionnaire were processed using the Certainty Factor. The results of this study are the results of interest and talent analysis based on 7 intelligence criteria and also the highest summary results from several criteria with one of the tests yielding a percentage of 93.58% in the field of linguistics.